2017
DOI: 10.1093/aje/kwx116
|View full text |Cite
|
Sign up to set email alerts
|

Effort-Reward Imbalance at Work and the Prevalence of Unsuccessfully Treated Hypertension Among White-Collar Workers

Abstract: We examined the association between effort-reward imbalance (ERI) exposure at work and unsuccessfully treated hypertension among white-collar workers from a large cohort in Quebec City, Canada. The study used a repeated cross-sectional design involving 3 waves of data collection (2000-2009). The study sample was composed of 474 workers treated for hypertension, accounting for 739 observations. At each observation, ERI was measured using validated scales, and ambulatory blood pressure (BP) was measured every 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In several studies, ambulatory blood pressure (ABP) was assessed during one or several working days [ 29 , 34 , 35 ], or even repeatedly in the frame of a prospective epidemiological study over up to seven years [ 36 , 37 , 38 , 39 , 40 ] in association with work stress measures. One of these studies performed in a group of 74 female and 26 male employees in Italy found no association of ERI with elevated ABP over two working days [ 35 ], whereas in the Vrijkotte et al study [ 29 ], an imbalance between effort and reward was associated with an average increase in systolic blood pressure (SBP) of 4 mmHg, and this increase was not restricted to work time, but persisted during leisure time and non-work days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, ambulatory blood pressure (ABP) was assessed during one or several working days [ 29 , 34 , 35 ], or even repeatedly in the frame of a prospective epidemiological study over up to seven years [ 36 , 37 , 38 , 39 , 40 ] in association with work stress measures. One of these studies performed in a group of 74 female and 26 male employees in Italy found no association of ERI with elevated ABP over two working days [ 35 ], whereas in the Vrijkotte et al study [ 29 ], an imbalance between effort and reward was associated with an average increase in systolic blood pressure (SBP) of 4 mmHg, and this increase was not restricted to work time, but persisted during leisure time and non-work days.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the double exposure of ERI and family obligations among women resulted in a significant rise in ABP after 5 years [ 40 ]. Moreover, it is instructive to know that in this prospective study, ERI was associated with significantly increased risks of untreated hypertension [ 39 ] and masked hypertension [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…This cohort has been described elsewhere. 13, 14 The study population was composed of all white collar workers from three large public insurance institutions in Canada. These organisations were chosen because they tend to have comparable activities as all three deliver insurance services to the general population.…”
Section: Methodsmentioning
confidence: 99%
“…Among indigenous people in Ontario (Canada), rates of cardiovascular disease and the presence of risk factors, including information about hypertension, were higher among people with lower incomes [32]. The negative role of adverse psychosocial factors on control of blood pressure among "white-collar" workers in Quebec (Canada) has also been proved [33]. In our study, hypertension was also much more common among widowers, uneducated, persons unsatisfied with living conditions and long-term unemployed people (p<0.001).…”
Section: Discussionmentioning
confidence: 99%